Cyclophosphamide versus etoposide in combination with total body irradiation as conditioning regimen for adult patients with Ph‐negative acute lymphoblastic leukemia undergoing allogeneic stem cell transplant: On behalf of the ALWP of the European Society for Blood and Marrow Transplantation. Issue 6 (30th March 2018) - Czyz, Anna; Labopin, Myriam; Giebel, Sebastian; Socié, Gerard; Apperley, Jane; Volin, Liisa; Reményi, Péter; Yakoub‐Agha, Ibrahim; Orchard, Kim; Michallet, Mauricette; Stuhler, Gernot; Chaganti, Sridhar; et al.
Abstract: Allogeneic hematopoietic cell transplantation (alloHCT) with myeloablative conditioning based on total body irradiation (TBI) is widely used for the treatment of adults with acute lymphoblastic leukemia (ALL). TBI is most frequently administered in combination with either cyclophosphamide (Cy/TBI) or etoposide (Vp/TBI). The goal of this study was to retrospectively compare these two regimens. Adult patients with Ph‐negative ALL treated with alloHCT in first or second complete remission who received Cy/TBI ( n = 1346) or Vp/TBI ( n = 152) conditioning were included in the analysis. In a univariate analysis, as compared to Cy/TBI, the use of Vp/TBI was associated with reduced incidence of relapse (17% vs. 30% at 5 years, P = .007), increased rate of leukemia‐free survival (60% vs. 50%, P = .04), and improved "graft versus host disease (GVHD) and relapse‐free survival" (GRFS, 43% vs. 33%, P = .04). No significant effect could be observed in terms of the incidence of nonrelapse mortality or acute or chronic GVHD. In a multivariate model, the use of Vp/TBI was associated with reduced risk of relapse (HR = 0.62, P = .04) while the effect on other study end‐points was not significant. In conclusion, conditioning regimen based on Vp combined with TBI appears more effective for disease control than the combination of Cy with TBI for adult patients with Ph‐negative ALL treated with alloHCT.